Effectiveness of a cardiac rehabilitation program on biomechanical, imaging, and physiological biomarkers in elderly patients with heart failure with preserved ejection fraction (HFpEF): FUNNEL + study protocol - Cuesta-Vargas, Antonio; Fuentes-Abolafio, Iván José; García-Conejo, Celia; Díaz-Balboa, Estibaliz; Trinidad-Fernández, Manuel; Gutiérrez-Sánchez, Daniel; Escriche-Escuder, Adrián; Cobos-Palacios, Lidia; López-Sampalo, Almudena; Pérez-Ruíz, Jose María; Roldán-Jiménez, Cristina; Pérez-Velasco, Miguel Angel; et al. (Springer Nature, 2023)
Patients with heart failure with preserved ejection fraction (HFpEF) have a low functional status, which in turn is a risk factor for hospital admission and an important predictor of survival in HFpEF. HFpFE is a heterogeneous syndrome and recent studies have suggested an important role for careful, pathophysiological-based phenotyping to improve patient characterization. Cardiac rehabilitation has proven to be a useful tool in the framework of secondary prevention in patients with HFpEF. Facilitating decision-making and implementing cardiac rehabilitation programs is a challenge in public health systems for HFpEF management. The FUNNEL + study proposes to evaluate the efficacy of an exercise and education-based cardiac rehabilitation program on biomechanical, physiological, and imaging biomarkers in patients with HFpEF.
Background: Patients with heart failure with preserved ejection fraction (HFpEF) have a low functional status, which in turn is a risk factor for hospital admission and an important predictor of survival in HFpEF. HFpFE is a heterogeneous syndrome and recent studies have suggested an important role for careful, pathophysiological-based phenotyping to improve patient characterization. Cardiac rehabilitation has proven to be a useful tool in the framework of secondary prevention in patients with HFpEF. Facilitating decision-making and implementing cardiac rehabilitation programs is a challenge in public health systems for HFpEF management. The FUNNEL + study proposes to evaluate the efficacy of an exercise and education-based cardiac rehabilitation program on biomechanical, physiological, and imaging biomarkers in patients with HFpEF. Methods: A randomised crossover clinical trial is presented among people older than 70 years with a diagnosis of HFpEF. The experimental group will receive a cardiac rehabilitation intervention for 12 weeks. Participants in the control group will receive one educational session per week for 12 weeks on HFpEF complications, functional decline, and healthy lifestyle habits. VO2peak is the primary outcome. Biomechanical, imaging and physiological biomarkers will be assessed as secondary outcomes. Outcomes will be assessed at baseline, 12 weeks, and 24 weeks. Discussion: Identifying objective functional parameters indicative of HFpEF and the subsequent development of functional level stratification based on functional impairment ("biomechanical phenotypes") may help clinicians identify cardiac rehabilitation responders and non-responders and make future clinical decisions. In this way, future pharmacological and non-pharmacological interventions, such as exercise, could be improved and tailored to improve quality of life and prognosis and reducing patients' hospital readmissions, thereby reducing healthcare costs. Trial registration: NCT05393362 (Clinicaltrials.gov).
Keywords: Sistema cardiovascular - Enfermedades; Cardiovascular rehabilitation; Frail elderly syndrome; Functional physical performance; Heart failure; Preserved ejection fraction; Sarcopenia